Computational fluid dynamics - Chung, T. J., 1929- (Cambridge, UK. : Cambridge University Press, 2010)
'In this second edition of Computational Fluid Dynamics, the author presents up-to-date treatments of all computational methods of fluid dynamics, while maintaining the original idea of including all computational fluid dynamics methods. The breadth of information sets this book apart from its competitors and allows the instructor to adopt this book, selecting only those subject areas of his or her interest. The second edition includes a new section on preconditioning for EBE-GMRES and a complete revision of the section on flow field-dependent variation methods, which demonstrates more detailed computational processes and includes additional example problems. Homework examples facilitate students and practitioners intending to develop a large-scale computer code'--
'The development of modern computational fluid dynamics (CFD) began with the advent of the digital computer in the early 1950s. Finite difference methods (FDM) and finite element methods (FEM), which are the basic tools used in the solution of partial differential equations in general and CFD in particular, have different origins. In 1910, at the Royal Society of London, Richardson presented a paper on the first FDM solution for the stress analysis of a masonry dam. In contrast, the first FEM work was published in the Aeronautical Science Journal by Turner, Clough, Martin, and Topp for applications to aircraft stress analysis in 1956. Since then, both methods have been developed extensively in fluid dynamics'--
Includes bibliographical references and index.
Keywords: Fluid dynamics -- Data processing